Plastic optical fibre sensor for spine bending monitoring with power fluctuation compensation - Mohd Anwar, Zawawi; O’Keeffe, Sinead; Lewis, Elfed (MDPI, 2013)
This paper presents the implementation of power fluctuation compensation for an intensity-based optical fibre bending sensor aimed at monitoring human spine bending in a clinical environment. To compensate for the light intensity changes from the sensor light source, a reference signal was provided via the light reflection from an aluminum foil surface fixed at a certain distance from the source fibre end tips. From the results, it was found that the investigated sensor compensation technique was capable of achieving a 2° resolution for a bending angle working range between 0° and 20°. The study also suggested that the output voltage ratio has a 0.55% diversion due to input voltage variation between 2.9 V and 3.4 V and a 0.25% output drift for a 2 h measurement. With the achieved sensor properties, human spine monitoring in a clinical environment can potentially be implemented using this approach with power fluctuation compensation